SMALL FARMS IN THE FRAMEWORK OF SUSTANABLE DEVELOPMENT OF THE AGRICULTURAL SECTOR IN THE REPUBLIC OF MOLDOVA - Alexandru STRATAN; Eugenia LUCASENCO; Alexandru CEBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The general well-being of small farms represents an important and actual issue for the Republic of Moldova. Taking into consideration that they are more likely to be exposed to hazards of different origin, it is becoming increasingly important to enhance their living and working conditions. The aim of the paper is to analyse the current situation of small farms in the Republic of Moldova in the context of sustainable development of the agricultural sector and emphasize their future possibilities of progress. For the purpose of the research, a survey has been carried out on a sample of 552 small farms from North, Centre and South regions of the Republic of Moldova. The main findings present prospects for development of small farms in the country under certain conditions, like: specialization in high added value production, efficientization of working time, modernization of farming activities, establishment of direct relations with the market, etc.